Pre-post accident analysis relates to pre-cursor emotion for driver behavior understanding - M. Nor, Norzaliza; Abdul Rahman, Abdul Wahab; Kamaruddin, Norhaslinda; Abdul Majid, Hariyati Shahrima (2011)
As a high rate of road accidents, a research study has been done on the causes of these accidents. Yet, driver behavior is one of the main reason for this predicament while emotion plays a vital role as it affect the driver behavior itself. However, studies on pre-cursor emotion and pre-post accident condition using Electroencephalogram (EEG) pattern are scarce. Hence, this paper proposed to analyze the pre-post accident analysis to determine the correlation between driver behavior and emotion through the 2-D affective space model: valance arousal approach (VAA). EEG machine has been applied to produce the brain waves that requires the drivers to drive in a different traffic condition by using driving simulator. The analysis results of VA for each driver exposed that pre- cursor emotion will affect the emotion in pre-accident whereas negative emotion appear frequently in post-accident compared to positive emotion. This exemplify that the understanding of pre-cursor emotion and its relationship towards driver behavior will help the driver to learn on how to control his/her emotions which can prevent an accident.